The effect of waste clay brick as a partial sand replacement on the mechanical properties of concrete - Ahmad Faizul, Ali (2017)
A brick is building material used to make walls, pavements and other elements in masonry construction. Waste clay brick are normally dumped as waste by the contractor at the construction project. Sand mining is the removal of sand from their natural place. Sand mining activity is deepen the river and can cause many environmental problems. The recycling of solid waste like waste clay brick as a partial sand replacement be the alternative way to reducing the sand mining activity. The research aims to investigate the waste clay brick on the properties of concrete. Firstly, the waste clay brick are collected from the building that has been destroyed or at construction site and finally crushed and graded in the range of standard sand. The objective of this experiment is to investigate the effect of waste clay brick as partial sand replacement on workability strength, compressive strength and flexural strength of concrete. The sample would be subjected to water curing for 7, 14 and 28 days. The finding show that 10% replacement is the suitable content of waste clay brick that can reach the targeted strength.